PENGARUH PERCEIVED RISK TERHADAP ONLINE TRUST DAN DAMPAKNYA TERHADAP ONLINE PURCHASE INTENTION (Studi pada konsumen marketplace di Indonesia) - Dita Puspitasari; I Made Bayu Dirgantara (Jurnal Akuntansi dan Pajak, 2023)
This study aims to analyze the influence of perceived risk factors that can affect online consumer trust and increase online purchase intention in the marketplace. Sampling was used using a purposive sampling technique, the total sample used was 349 respondents who were consumers who had made purchases at marketplaces in Indonesia and had more than one marketplace account. The data analysis technique used in this study was SEM (Structural Equation Model) analysis with the AMOS program, and the data collection technique used a questionnaire. The results of the study show that perceived risk has a negative effect on online purchase intention variables. Online trust has a positive effect on online purchase intention. Online trust does not mediate the effect of perceived risk. Keywords : perceived risk, online trust, online purchase intention